Patronage Project: The Performance of an Extensionist Project in Open Regime in Londrina County - Ferreira da Silva, Ana Lucia; Garcia Cavagnari, Alinne; Simitan Claro de Oliveira, Daniela; Luvison Nunes da Silva, Muriel; dos Santos Almeida, Nayara Aparecida (Guará Journal, 2019)
The present article aims presenting the actions developed through the  Patronage  Project  -  Londrina. The  project  is  composed  by  a  multidisciplinary team of graduated, recently graduated and advisors in their respective areas, which are: Law, Psycology, Administration, Social Service and Pedagogy in the State University of Londrina (PR), who act in a penal execution organ of open regime, denominated as Penitentiary Patronage of Londrina (PLDA). The unit is responsible for the fiscalization and attendance of graduates and beneficiaries with alternative  sentences  and  penalties in  semi-open  regime,  as  much  as  the  attendance and the  pursuit  so  that  the  public  is  recognised  as citizens with rights. Supported by a data collection of the own unit system;  and  by  the  life  experience  of  the scholarshippers  from  the  pedagogic area of this project, a quantitive and qualitative analysis is presented in relation to the work and actions developed since the year  of  2014,  when  this  extension  project  began, until  2018.  From  these data it will be presented the results obtained by the pedagogy section in this space of time in the district of Londrina.
Keywords: Extension project; Penitentiary Patronage of Londrina; Semi-open penal execution; Pedagogic section